The COVID-19 pandemic and international federation of medical students’ association exchanges: thousands of students deprived of their clinical and research exchanges - Yassamine Bentata (Medical Education Online, 2020)
The repercussions of the COVID-19 pandemic for medical students are enormous and not limited to the interruption of courses in medical schools and/or hospital training rotations, the introduction of teaching exclusively online, postponement of examinations, and of the new academic year, but extend beyond that. The mobility of students within the framework of the International Federation of Medical Students’ Associations (IFMSA) is also strongly affected by the unexpected interruption of this program and the deprivation of thousands of students worldwide of this fine opportunity for training, exchange and sharing. The International Federation of Medical Students’ Associations (IFMSA) was founded in 1951 and currently maintains 135 National Member Organizations (NMOs) from 125 countries, representing a network of 1.3 million medical students around the globe. Moroccan students, members of IFMSA like students from other countries, are also concerned. Clinical and research exchanges, carried out under the auspices of the IFMSA, allow all the students to discover the health care and medical education systems of another country in a different sociocultural environment. To maintain student motivation and deal with the repercussions of cancelled exchanges, IFMSA could propose online training programs, adapted to student needs during this period of confinement and deconfinement from June to September 2020.